(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
The department of Caquetá has 63,666 horses, which 439 of them are in Florencia’s municipality. They are dedicated to working as driver horses, as this work is the economic support of many families in the country. This research study’s objective was to determine the biochemical reference parameters for liver transaminases (Aspartate aminotransferase, Gamma-glutamyltransferase, Alkaline phosphatase, and total plasma proteins) of horses traction from municipality of Florencia, Caquetá. The Veterinary Clinical Laboratory of the Veterinary Medicine and Zootechnics program of Amazonia’s university collected 79 blood samples. These samples belonged to 23 female equines and 56 male equines. This study used descriptive analysis of each of the variables through central tendency (mean and median). Subsequently, the comparative t-test was applied for means of two paired samples between females and males equines. The reference value and standard deviation (SD) of each of the variables were (AST: 217.1 ± 47.07; GGT: 11.7 ± 3.09; ALP: 293.2 ± 108.05; TPP: 72.7 ± 7.45). Finally, the researchers did not find significant differences (P> 0.05) between females and males. The values generated in this study can be considered as a reference for the driver horse of Florencia municipality, and they are a sample of the equines’ physiological and environmental conditions.